Effect of magnetic islands on profiles, flows, turbulence and transport in nonlinear gyrokinetic simulations. (3rd February 2017) - Navarro, A Bañón; Bardóczi, L; Carter, T A; Jenko, F; Rhodes, T L
Abstract: Neoclassical tearing modes have deleterious effects on plasma confinement and, if they grow large enough, they can lead to discharge termination. Therefore, they impose a major barrier in the development of operating scenarios of present-day tokamaks. Gyrokinetics offers a path toward studying multi-scale interactions with turbulence and the effect on plasma confinement. As a first step toward this goal, we have implemented static magnetic islands in nonlinear gyrokinetic simulations with theGENE code. We investigate the effect of the islands on profiles, flows, turbulence and transport and the scaling of these effects with respect to island size. We find a clear threshold island width, below which the islands have little or no effect while beyond this point the islands significantly perturb flows, increase turbulence and transport. Additionally, we study the effect of radially asymmetric islands on shear flows for the first time. We find that island induced shear flows can regulate turbulent fluctuation levels in the vicinity of the island separatrices. Throughout this work, we focus on experimentally relevant quantities, such as rms levels of density and electron temperature fluctuations, as well as amplitude and phasing of turbulence modulation. These simulations aim to provide guidelines for interpreting experimental results by comparing qualitative trends in the simulations with those obtained in tokamak experiments.